Concurrent adaptations in maximal aerobic capacity, heat tolerance, microvascular blood flow and oxygen extraction following heat acclimation and ischemic preconditioning. (October 2020) - Waldron, M.; Papavasileiou, G.; Jeffries, O.; Nevola, V.; Heffernan S, M.; Kilduff, L.; Tallent, J.
Abstract: We investigated the effects of: 1) Ischemic pre-conditioning (IPC) plus a concurrent five-day heat acclimation + IPC (IPC + HA), 2) five-day HA with sham IPC (HA), or 3) control (CON) on thermoneutral measurements of endurance performance, resting measures of skeletal muscle oxygenation and blood flow. Twenty-nine participants were randomly allocated to three groups, which included: 1) five-days of repeated leg occlusion (4 x 5-min) IPC at limb occlusive pressure, plus fixed-intensity (55% V ˙ O2max ) cycling HA at 36 °C/40% humidity; 2) HA plus sham IPC (20 mmHg) or 3) or CON (thermoneutral 55% V ˙ O2max plus sham IPC). In IPC + HA and HA, there were increases in maximal oxygen consumption (O2max ) (7.8% and 5.4%, respectively; P < 0.05), ventilatory threshold (VT ) (5.6% and 2.4%, respectively, P < 0.05), delta efficiency (DE) (2.0% and 1.4%, respectively; P < 0.05) and maximum oxygen pulse (O2 pulse-Max) (7.0% and 6.9%, respectively; P < 0.05) during an exhaustive incremental test. There were no changes for CON ( P > 0.05). Changes ( P < 0.05) in resting core temperature (TC ), muscle oxygen consumption (m V ˙ O2 ), and limb blood flow (LBF) were also found pre-to-post intervention among the HA and IPC + HA groups, but not in CON ( P > 0.05). Five-days of either HA or IPC + HA can enhance markers of endurance performance in cooler environments, alongside improved muscle oxygen extraction, blood flow, exercising muscle efficiency and O2 pulse at higher intensities, thus suggesting the occurrence of peripheral adaptation. Both HA and IPC + HA enhance the adaptation of endurance capacity, which might partly relate to peripheral changes. Highlights: Five-days of heat acclimation alone (HA) or mixed with ischemic preconditioning (IPC + HA) enhances endurance in the cool. Changes in endurance were coupled with preferable increases in muscle efficiency and O2 pulse at higher intensities. Both HA and IPC + HA also increased muscle microvascular O2 extraction and blood flow at rest. Despite non-significant effects, the change in the IPC + HA group indicate that it could be used as an adjunct, non-thermal intervention.